Experimental analysis for optimum thermal performance and thermophysical parameters of MWCNT based capric acid PCM by using T-history method - Yadav C.; Rekha Sahoo R. (My University, 2025)
In the present experimental study, with the help of the T-history method, the thermophysical parameters, and the thermal performance for (0–0.025%) vol. fractions of multiwall carbon nanotubes (MWCNT) in capric acid phase change material based thermal energy storage system has been investigated. Application of the T-history method for the evaluation of thermophysical parameters states that the specific heat capacity and thermal conductivity increases for both liquid and solid phase of the mixtures up to the addition of 0–0.02% vol. fraction of multiwall carbon nanotubes in capric acid phase change material. However, the heat of fusion decreases with an increase in MWCNT, and pure capric acid has 51.57% higher heat of fusion compared to 0.02% vol. fraction of MWCNT based capric acid PCM. Also, 0.02% vol. fraction of multiwall carbon nanotubes based capric acid PCM has 31.29% and 14.4% higher liquid and solid thermal conductivity, respectively, compared to pure capric acid. Furthermore, the present work also extends to particle size analysis along with distributions determined by the dynamic light scattering method for various vol. fractions of MWCNT based capric acid phase change material. Comparing the thermal performance analysis, 0.02% vol. fraction MWCNT in capric acid PCM has a 30.97% higher heat transfer rate compared to pure capric acid PCM within the time duration of 3 min. Also, the addition of MWCNT beyond 0.02% vol. fraction in capric acid, increases the particle settlement rate rapidly, which may be concluded that 0.02% vol. fraction of MWCNT in capric acid PCM based thermal energy storage system results in an optimum thermophysical property and thermal performance. © 2020 Elsevier B.V.